Achievement of learning volleyballs: Correlation between mental hygiene and the level of physical fitness - Rola Angga Lardika; Daharis; Ardiah Juita; Zainur (Journal Sport Area, 2021)
Mental hygiene and physical fitness are very important concerning volleyball learning achievement. This study aims to determine volleyball learning achievement which is correlated with (mental hygiene) and level of physical fitness. This research is a type of quantitative research with a correlation approach. The population in this study was 78 students of class 1A, Department of Physical Education, Health, and Recreation, Universitas Riau. The author will use only a portion to represent the existing population. The sampling technique of this research is purposive sampling. The number of samples is 40 people. Methods of data collection uses survey methods with test and measurement techniques. The statistical analysis method used in this study is multi-correlation. It is using a regression analysis test because it analyzes the relationship of more than 2 test variables. The instrument used was a test of physical fitness, mental health questionnaire test, and the results of learning achievement scores of volleyball subject. The mental hygiene instrument has a validity level of 0.595 and a reliability level of 0.522. while physical fitness instruments are adopted of the Indonesian Physical Fitness Test. Test and measurement data were processed using the multiple regression analysis methods. Based on the research results, it can be concluded that physical fitness and mental hygiene have a significant relationship with volleyball learning achievement. These results explain the importance for educators to be able to pay attention to students to improve volleyball learning achievement through providing subject matter by paying attention to physical fitness, using group games to instill a social spirit, sportsmanship, and students' confidence.